2021
DOI: 10.1002/cam4.4420
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to follow‐up after the exit cervical cancer screening test at age 60–64: A nationwide register‐based study

Abstract: Background: In Denmark, human papillomavirus (HPV) testing has replaced cytology in primary cervical cancer screening for women aged 60-64; at this age, women are invited for the last (exit) screening test within the national organized program. Aim:We investigated the adherence of these women to the recommended follow-up after a non-negative (positive or inadequate) HPV test and the overall resource use during that follow-up. Materials & Methods:We included all 2926 women aged 60-64 years with nonnegative HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In England, one of the options proposed for primary screening is for women aged over 65 who test HPV-positive but show no abnormalities from cytology or colposcopy to exit the screening programme. In Denmark, nearly half of the women aged 60–64 did not receive adequate follow-up after a positive HPV test [ 15 ]. Our findings suggest that this is not safe.…”
Section: Discussionmentioning
confidence: 99%
“…In England, one of the options proposed for primary screening is for women aged over 65 who test HPV-positive but show no abnormalities from cytology or colposcopy to exit the screening programme. In Denmark, nearly half of the women aged 60–64 did not receive adequate follow-up after a positive HPV test [ 15 ]. Our findings suggest that this is not safe.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study by Andersen and colleagues found that HPV screening almost doubled the sensitivity but somewhat lowered the specificity in detection of severe cervical lesions compared with cytology ( 43 ). In addition, the risk of acquiring a new infection at these ages is lower than in younger age groups ( 44, 45 ) which is partly why some countries, including Denmark and Australia, have utilized HPV tests as exit tests ( 46, 47 ). After a negative exit test, the screening program can cease for the individual as the protection is thought to be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of inadequate follow-up of abnormal cervical screening results in Norway is currently unknown, but a recent American study estimated that as much as half of patients with discordant HPV and cytology results do not receive follow-up according to guidelines [ 15 ]. In Denmark, guideline-accordant follow-up of cervical screening exit tests was lower among women with previous abnormal test results [ 16 ]. Delegating follow-up of women who need individual assessments to gynaecologists with colposcopy expertise who also have access to all test results, could ease correct follow-up and alleviate GPs of their largest reported challenge with the NCCPS.…”
Section: Discussionmentioning
confidence: 99%
“…Delegating follow-up of women who need individual assessments to gynaecologists with colposcopy expertise who also have access to all test results, could ease correct follow-up and alleviate GPs of their largest reported challenge with the NCCPS. However, follow-up by gynaecologists may not increase guideline adherence [ 16 ], and the cost-effectiveness of changing the scheme would have to be evaluated.…”
Section: Discussionmentioning
confidence: 99%